Computer simulation to determine cut-off point between generating and purchasing electric energy - Miravalles, Lemuel M. (1971)
A mathematical model of the power plant operations of the Angeles Electric Corporation is developed. By controlling the amount of energy purchased from the National Power Corporation and the amount and source of generated energy, the model is used to investigate the effects of changes in policy on the total variable cost and unit cost of AEC electric energy. The results and conclusions of the study are applicable only with the assumptions made and given data used.
Thesis (M.E.)--University of the Philippines.
Keywords: Angeles Electric Corporation, Angeles City; Electric power-plants -- Costs. -- Pampanga